Identifying and Ranking the Risks Involved In the Construction Projects of High-Rise Buildings of Mashhad - Mahdi Jahanshahi Javaran; Babak Panahi (مهندسی و مدیریت ساخت)
The current research aims to identify and rank the risks involved in the construction projects of high-rise buildings of Mashhad using Analytic Hierarchy Process (AHP) model. To achieve the research objective, through reviewing the literature, the different criteria and dimensions of the risks involved in construction industry and high-rise building projects were identified and on the basis of those criteria and dimensions, the research questionnaire was prepared and its reliability and validity were verified. The statistical population consisted of the entire managers of the construction companies of high-rise building of Mashhad, which 45 individuals of them were identified and based on whole-counting sampling method, all of them were selected as the research statistical sample. After data collection, to answer the research questions, various analytical methods including Confirmatory Factor Analysis (CFA) and Analytic Hierarchy Process (AHP) were utilized. The generated results of CFA revealed that the existing risks in the construction projects of high-rise buildings can be categorized into two taxonomies of internal and external risks. The generated results of AHP indicated that the internal risks are more important than the external risks of the construction projects of high-rise buildings of Mashhad.